FAKTOR YANG MEMPENGARUHI TINGKAT KETAHANAN PANGAN DESA (Studi Kasus di Kabupaten Malang) - Lien Damayanti (Universitas Tadulako, 2007)
This research aims (1) to analysis factors affecting the level of food tenacity both directly and indirectly, (2) to analysis thecorrelation and the influence between availability, food access and livelihood, nutrition and health, and food susceptibility, and (3) toanalysis the effect of availability, food access and livelihood, nutrition and health, and food susceptibility on the level of food tenacityeither partial or combination. This research conducted in 3 sub-district at Malang District: (1) Kepanjen, (2) Pakisaji, and (3) SumberPucung with 30 villages. The research carried out using Path analysis with indicators: (1) Availability, (2) Food access andLivelihood, (3) Nutrition and Health, and (4) Food susceptibility. The results of analysis show that only 3 factors significantly affectthe level of food tenacity such as food access and livelihood, nutrition and health, and food susceptibility. However, indicator ofavailability shown no significant. The Successful of food security can be achieved if food could reach to household level.Keywords: Agriculture, food in security and modeling